2018
DOI: 10.3847/1538-4357/aab36d
|View full text |Cite
|
Sign up to set email alerts
|

Sun-to-Earth MHD Simulation of the 2000 July 14 “Bastille Day” Eruption

Abstract: Solar eruptions are the main driver of space-weather disturbances at the Earth. Extreme events are of particular interest, not only because of the scientific challenges they pose, but also because of their possible societal consequences. Here we present a magnetohydrodynamic (MHD) simulation of the 14 July 2000 "Bastille Day" eruption, which produced a very strong geomagnetic storm. After constructing a "thermodynamic" MHD model of the corona and solar wind, we insert a magnetically stable flux rope along the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 191 publications
5
124
0
2
Order By: Relevance
“…Especially looking at different spacecraft locations, we found that the magnetic cloud structure that is arriving at 1 au is sensitive to a change of only a few degrees. A similar conclusion has recently been highlighted by Török et al (2018). Keeping in mind that the error in kinematic CME parameters obtained from observations, such as latitude and longitude, can have errors larger than the discussed shift from Earth to the virtual spacecraft, it is needed to proceed with care when performing only one run with the LFFS model.…”
Section: Discussion and Summarysupporting
confidence: 56%
“…Especially looking at different spacecraft locations, we found that the magnetic cloud structure that is arriving at 1 au is sensitive to a change of only a few degrees. A similar conclusion has recently been highlighted by Török et al (2018). Keeping in mind that the error in kinematic CME parameters obtained from observations, such as latitude and longitude, can have errors larger than the discussed shift from Earth to the virtual spacecraft, it is needed to proceed with care when performing only one run with the LFFS model.…”
Section: Discussion and Summarysupporting
confidence: 56%
“…It should be noted, however, that MHD simulations are capable of incorporating the internal CME magnetic field (e.g. Torok et al, 2018), although it is difficult to implement in a forecasting situation and is not currently used operationally. The effect of non-hydrodynamic effects on CME arrival times has yet to be quantified, although it is expected to be relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…While a polytropic stellar wind outflow naturally creates a significant mass density gradient between the openflux regions (coronal holes) and the closed-field corona (the helmet streamer belt), a more realistic treatment of the internal energy equation is expected to increase this density contrast for both the quiet-Sun and active regions (e.g. Török et al 2018). The isothermal model for our stellar atmosphere has two main consequences for our simulation results: first, on the structure and intensities associated with our synthetic EUV and soft X-ray emission profiles; second, on the interaction between the CME and the background wind, including the properties of the CME-driven shock.…”
Section: Discussionmentioning
confidence: 99%